FAKTOR-FAKTOR YANG MEMPENGARUHI JOB SATISFACTION DI MODERASI OLEH WORKPLACE RELATIONSHIPS - AGATHA SERAFIM WULAN DEFANI; SETIA TJAHYANTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to analyze the influence of payment and compensation, promotion, working environment, and workplace fairness on job satisfaction, with workplace relationships as a moderating variable. The research employs a causal and descriptive research design. The object of the study is the Regional Civil Service Agency (BKD) of DKI Jakarta Province. Data were collected using questionnaires and analyzed using SEM-PLS. The sampling technique used was purposive sampling, with a total of 97 respondents. Based on the results, payment and compensation have a significant influence on job satisfaction, promotion has a significant influence on job satisfaction, the working environment has a significant influence on job satisfaction, and workplace fairness also significantly affects job satisfaction. Furthermore, workplace relationships have a positive moderating effect on the relationship between payment and compensation and job satisfaction. Workplace relationships also positively moderate the relationship between promotion and job satisfaction, the relationship between working environment and job satisfaction, and the relationship between workplace fairness and job satisfaction.